COMPARISON OF MULTIPLEX SINGLE ROUND PCR AND MICROSCOPY IN DIAGNOSIS OF AMOEBIASIS - Sri-Hidajati, BS; Basuki, Sukmawati; Pusarawati, Suhintam; Kusmartisnawati, Kusmartisnawati; Rossyanti, Lynda; Sulistyowati, Sri Wijayanti; Kartikasari, Dwi Peni; Arwati, Heny; Tantular, Indah; Fardah, Alpha; Darma, Andy; Handajani, Retno; et al. (African Journal of Infectious Diseases (AJID), 2018)
Background: Amoebiasis, the cause of dysentery and extra-intestinal abscesses, now becomes second fatal parasitic disease in the world. As routine microscopic diagnosis cannot differentiate causative Entamoeba histolytica from non-pathogenic E. dispar and E. moshkovskii, better diagnosis has to be searched. Materials and Methods: Multiplex single round PCR was tested and compared with results of microscopy of wet preparation on 30 samples of diarrheic stools and extra intestinal lesions from amoebiasis suspected patients. Results: Microscopy examination showed that 21 (70%) of the samples were positive for E. histolytica/E. dispar/E. moshkovskii complex and 18 (86%) of them contained hematophagous trophozoites. Multiplex single round PCR showed 12 positive results, from which seven were positive for E. histolytica, two were positive for E. moshkovskii, and three showed mixed of E. histolytica and E. moshkovskii. No samples were positive for E. dispar. High positive rate of microscopy might be related with highly suspected amoebiasis cases, while lower positive PCR might be caused by low parasite density and time-related trophozoite disintegration. Conclusion: The study showed that multiplex single-round PCR is a valuable diagnostic tool for species differentiation, but cannot replace microscopy in the diagnosis of amoebiasis because of its low sensitivity and impossibility to discriminate the form of E. histolytica and whether it is in the disease-causing stage, while microscopic examination is capable to demonstrate the presence of hematophagous trophozoites that indicates it is invasive and at the disease-causing stage of E. histolytica.